TINDAK PIDANA ROMANCE SCAM DALAM SITUS KENCAN ONLINE DI INDONESIA - Tasya Salsabilah (Universitas Udayana, 2021)
This study aims to examine the factors that cause the crime of romance scam on online dating sites in Indonesia and how legal protection is for victims. The research method used is a normative juridical approach through a statutory approach and a conceptual approach. The factors causing the romance scam are due to economic and external factors, namely the opportunity. The legal protection provided by the Law of the Republic of Indonesia Number 19 of 2016 concerning Electronic Information and Transactions in the form of settlement of cases and imposing criminal sanctions given to suspects or defendants. The form of legal protection for victims of romance scam is the provision of rights and obligations. Keywords:Fraudsters, Online Dating Sites, Legal Protection